Metagenomics-based study of rhizospheric microorganisms of Poa alpigena L. in Qinghai Lake, Ganzi River Plateau - Wei, Bo; Xu, Qianqian; Kong, Junfei; Su, Xu; Chen, Kelong; Wang, Hengsheng (Frontiers in Plant Science, 2025)
IntroductionPoa alpigena Lindm., a dominant forage grass on the Tibetan Plateau, plays a critical role in livestock production and grassland restoration. This study investigates the rhizospheric and non-rhizospheric soil microorganisms of Poa alpigena L. in the Ganzi River area of the Qinghai Lake basin using metagenomic sequencing to understand their diversity and potential ecological functions.MethodsSoil samples were collected from rhizospheric and non-rhizospheric areas of Poa alpigena L. using the S-type five-point sampling method. DNA was extracted, and metagenomic sequencing was performed using the BGISEQ-500 platform. Alpha and Beta diversity analyses were conducted, and LEfSe analysis was used to identify differentially abundant microbial taxa and metabolic pathways.ResultsA total of 5,681 microbial species across 1,606 genera, 521 families, 61 phyla, and 246 orders were identified. Non-rhizospheric soils exhibited higher species richness than rhizospheric soils. Proteobacteria was the most abundant phylum in both soil types. Rhizospheric soils showed significant enrichment in pathways related to antibiotic biosynthesis, carbon metabolism, and methane metabolism, while non-rhizospheric soils were enriched in quorum sensing and drug-metabolizing pathways.DiscussionThe findings highlight the selective influence of Poa alpigena L. on soil microbial communities and their potential role in mitigating methane emissions. The study provides a foundation for understanding the ecological functions of soil microorganisms in alpine meadows and supports sustainable grassland management practices.